RESTORATIVE JUSTICE UNDER INDONESIA'S NEW CRIMINAL CODE: BETWEEN PENAL REFORM AND LEGAL CERTAINTY - Henny Saida Flora (Journal of Strafvordering Indonesian, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (hereinafter referred to as the National Criminal Code) marks a paradigmatic transformation of Indonesian criminal law from the retributive legacy of the colonial Wetboek van Strafrecht to a more humanistic and recovery-oriented model. One of the central ideas promoted in this reform is restorative justice, which places the restoration of relationships between perpetrators, victims, and society as the goal of punishment, rather than merely retribution. This article examines how restorative justice is normatively constructed in the National Criminal Code and how this concept interacts with the principle of legal certainty that has been the foundation of the legalistic criminal law system. Using normative legal research methods through legislative, conceptual, and comparative approaches, this article finds that the National Criminal Code accommodates restorative justice through various instruments, including the recognition of existing law in society, judicial forgiveness (rechterlijk pardon), alternative non-imprisonment sentences, and space for settlement outside the formal judicial process. However, the formulation of these norms remains general and leaves law enforcement officials with ample discretion, potentially leading to disparities in implementation and tensions with the principles of legality and legal certainty. This article recommends the need for more operational implementing regulations, strengthened institutional capacity, and adequate judicial oversight to ensure the consistent application of restorative justice without compromising legal certainty and the protection of victims' rights.